2006
DOI: 10.1111/j.1479-828x.2006.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum‐assisted delivery: An analysis of traction force and maternal and neonatal outcomes

Abstract: Safety recommendations for vacuum-assisted delivery focus on limiting the number of pulls and the duration of the procedure. With the introduction of the Kiwi OmniCup vacuum extractor incorporating a Traction Force Indicator, it is now possible to reliably monitor and control the amount of traction force exerted on the fetal scalp. The OmniCup was used in a prospective observational study of 119 vacuum-assisted deliveries in nulliparous women to establish practical guidelines for safe practice in typical clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 10 publications
2
49
1
2
Order By: Relevance
“…21 In a study by Vacca A. et al, among 119 attempted vacuum deliveries, there were 80% of nullipara and their neonates were delivered safely with vacuum extractor. 22 In our study, the principal cause of maternal morbidity was genital tract injuries in 6.7% followed by primary PPH in 3.8% which is similar to findings in the study by Hafeez 18,20,21 The fetal morbidities like cephalohematoma due to vacuum extractor has good fetal outcome with its subsidence in a few days. Birth asphyxia with vacuum application is primarily due to the result of prolonged second stage rather than vacuum use.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…21 In a study by Vacca A. et al, among 119 attempted vacuum deliveries, there were 80% of nullipara and their neonates were delivered safely with vacuum extractor. 22 In our study, the principal cause of maternal morbidity was genital tract injuries in 6.7% followed by primary PPH in 3.8% which is similar to findings in the study by Hafeez 18,20,21 The fetal morbidities like cephalohematoma due to vacuum extractor has good fetal outcome with its subsidence in a few days. Birth asphyxia with vacuum application is primarily due to the result of prolonged second stage rather than vacuum use.…”
Section: Discussionsupporting
confidence: 89%
“…7,19 Compared to other studies, our neonates had lesser number of cephalohematoma; 4.84% (n=5) versus 10.4% (n=7) in a study by Hafeez et al, 18% (n=38) in another study by Yakasai et al 7,16 Our study had similar results to that of Giri et al (3% cephalohematoma, 20% birth asphyxia) and Vacca A. et al (8.4% cephalohematoma). 18,22 Our result had similar rate of neonatal morbidity (25%) compared to that of Hafeez et al (22.1%) and less morbidity compared to that of Yakasai et al (31%). 7,16 …”
Section: Discussionsupporting
confidence: 75%
“…However, there is no established definition of this moderate traction, neither in clinical practice nor in the literature, and observed levels of force vary between studies. Two studies on plastic cup extractions suggest that the majority of deliveries require no more than the force equivalent to 11,5 kg (approximately 112 Newton)[6, 7]. Our research group found a different result in an observational study of 200 metal cup extractions, with average peak traction forces of 176, 225 and 241 N, depending on subjective category as easy, average or strong extraction respectively[8].…”
Section: Introductionmentioning
confidence: 86%
“…Cet indicateur mesure de manière fiable les forces imposées au cours de l'extraction [13]. L'application de forces supérieures à 13,5 kg pourrait augmenter les risques de survenue de complications maternelles et néonatales [14]. Ainsi, l'indicateur de traction pourrait permettre de mieux contrôler la force au cours du geste.…”
Section: Quels Sont Les Avantages Et Inconvénients De La Ventouse Kiwunclassified